The Role of Modern Technologies in Teaching the Mother Tongue (Eurasian Journal of Learning and Academic Teaching, 2023)
This article discusses the role of modern technologies in teaching the mother tongue. Language is not merely a tool for communication; it is the essence of cultural identity and heritage. In an increasingly globalized world, preserving and teaching one's mother tongue has become a vital endeavor. Modern technologies, ranging from interactive apps to virtual classrooms, have revolutionized the process of language education